What are They?: Book for Me to read - Ainsworth, Ruth and Ridout, Ronald (Purnell, 1965)
This book is to help children to read themselves.It will help you cope with this very real problem of persuading your child to make a start with continuous reading.
Keywords: Juvenile literature-Fiction